A cross-sectional study on the evaluation of laboratory analytical quality performance in a tertiary medical college in Eastern India - Sayani Chaudhuri (Asian Journal of Medical Sciences, 2025)
Background: Six Sigma is a powerful management tool that can be used in the laboratory to assess the quality of performance in the analytical phase.